Mobile health solutions in developing countries: a stakeholder perspective. Issue 3 (2nd July 2020) - Eze, Emmanuel; Gleasure, Rob; Heavin, Ciara
Abstract: Infrastructural deficiencies, limited access to medical care, and shortage of health care workers are just a few of the barriers to health care in developing countries. mHealth has the potential to overcome at least some of these challenges. To address this, a stakeholder perspective is adopted and an analysis of existing research is undertaken to look at mHealth delivery in developing countries. This study focuses on four key stakeholder groups i.e., health care workers, patients, system developers, and facilitators. A systematic review identifies 108 peer-reviewed articles, which are analysed to determine the extent these articles investigate the different types of stakeholder interactions, and to identify high-level themes emerging within these interactions. This analysis illustrates two key gaps. First, while interactions involving health care workers and/or patients have received significant attention, little research has looked at the role of patient-to-patient interactions. Second, the interactions between system developers and the other stakeholder groups are strikingly under-represented.